2019
DOI: 10.1002/jcp.29367
|View full text |Cite|
|
Sign up to set email alerts
|

miR‐188‐5p suppresses cellular proliferation and migration via IL6ST: A potential noninvasive diagnostic biomarker for breast cancer

Abstract: Previously, serum miR-188-5p is differentially expressed in breast cancer, but the diagnostic potential of circulating miR-188-5p as well as its regulatory mechanism in breast cancer remain uncertain. Herein, serum miR-188-5p was detected by real-time polymerase chain reaction in patients with breast cancer, breast fibroadenoma, and healthy subjects.Circulating miR-188-5p was abnormally elevated in patients with breast cancer as compared with these other two groups, and was reduced in patients with breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…MiR-373 was shown to enhance cell migration by suppressing ITGA2, the lack of which plays a relevant role in metastasis spread [85]; moreover, it was found hyper-expressed in TNBC [86]. Multiple roles were reported for miR-188, which negatively regulated cell proliferation and migration by targeting IL6ST [87] or enhanced apoptosis by suppressing the anti-apoptosis and pro-survival Rap2c [88].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-373 was shown to enhance cell migration by suppressing ITGA2, the lack of which plays a relevant role in metastasis spread [85]; moreover, it was found hyper-expressed in TNBC [86]. Multiple roles were reported for miR-188, which negatively regulated cell proliferation and migration by targeting IL6ST [87] or enhanced apoptosis by suppressing the anti-apoptosis and pro-survival Rap2c [88].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-188-5p is involved in cell proliferation and tumor growth in a variety of cancers. 10,[14][15][16] The results of cell functional experiments showed that high expression of miR-188-5p promoted the viability, cell cycle progression, proliferation, and tumor growth, and inhibited apoptosis in APL cells. In contrast, the effect of miR-188-5p silencing on the proliferation, apoptosis, and tumor growth was opposite to that of the highly expressed miR-188-5p phenotype in APL cells.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 It has been reported that miR-188-5p in Keloids inhibits cell proliferation and invasion via PI3K/ Akt/MMP-2/9 signaling 34 and in chronic myeloid leukemia-induced cell apoptosis by repressing the PI3K/AKT signaling. 16 The above results suggest that miR188-5p was involved in the activation of the PI3K/AKT/mTOR signaling pathway. CD2AP links actin to PI3K kinase activity to extend epithelial cell height and constrain cell area.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Wang et al reported that circulating miR-188-5p was upregulated in BC patients and associated with TNM of BC; interestingly, miR-188-5p was downregulated in BC MDA-MB-231 and MCF-7 cells. Moreover, using gain-of-and loss-of-function analyses of miR-188-5p in breast cancer cells the authors demonstrated that miR-188-5p inhibited the proliferation and invasion of BC MDA-MB-231 cells via targeting IL6ST (21). However, we demonstrated that the expression of miR-188-5p was drastically downregulated in BC tissue specimens, which was also decreased in BC cell lines, MDA-MB-231, BT549 and MCF-7, compared to normal breast epithelial cell line MCF-10A.…”
Section: Discussionmentioning
confidence: 99%